Optimization of gain flattened C-band EDFA using macro-bending - Hajireza, P.; Emami, S.D.; Abbasizargaleh, S.; Harun, Sulaiman Wadi; Abdul-Rashid, H.A. (IOP Publishing, 2010)
Optimization of gain flattened C-band erbium-doped fiber amplifier (EDFA) using a macro- bending method with an improved gain flatness and bandwidth is demonstrated. The optimization for gain flatness and bandwidth was achieved by varying the bending radius and the length of the doped fiber. In the optimized condition, the gain saturation effect as well as the energy transfer from shorter wavelengths to longer wavelengths resulted in a flattened and broadened gain profile in the C-band region. The amplifier was optimized to a 9 m long erbium-doped fiber (EDF) with erbium ion concentration of 1100 ppm and bending radius of 6.5 mm. The gain variation of the EDFA is obtained within +/- 1 dB over 25 nm bandwidth of C-band region.